Construction of Teaching Quality Evaluation System of Sports Human Science from the Perspective of Positive Psychology - Xue Han, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The traditional teaching quality evaluation system lacks the introduction of experiential education. The perspective of positive psychology is a part of experiential education. The evaluation system based on positive psychology is established, and the evaluation matrix is established to evaluate the teaching quality of sports human science by quantifying the data. Finally, an example is given to prove that the evaluation system can meet the requirements of teaching quality evaluation.